STUDY ON MAGNETIC SUSCEPTIBILITY OF CO(II) COMPLEXES AND ELECTRONIC SPECTRA OF CO(II) COMPLEXES - Ajit Kumar, (International Journal of Innovations in Engineering Research and Technology, 2021)
The ground state of octahedral Co(II) complex is 4T1g. The high spin octahedral Co(II) Complexes have magnetic moment in the range of 4.6-5.3 B.M. as reported by many workers. The high values of magnetic moment are in the favour of large orbital contribution.Several Workers22-24 observed the magnetic moment values of many Co(II) complexes within the range of 5.00 – 5.22 B.M. These values indicate that the complexes of Co(II) are high spin complexes.The magnetic moment values of several Co(II) complexes were reported by Stoufer and co-workers25 which fall within the range of 2.36 - 3.72 B.M. These low values of magnetic moment of octahedral Co(II) complexes may be due to the occurrence of equilibrium mixture in two spin states. The low magnetic moment values of Co(II) octahedral complexes were further explained by Stoufer on the basis of large tetragonal distribution along Z axis.